2004
DOI: 10.1038/sj.leu.2403399
|View full text |Cite
|
Sign up to set email alerts
|

Report of 34 patients with clonal chromosomal abnormalities in Philadelphia-negative cells during imatinib treatment of Philadelphia-positive chronic myeloid leukemia

Abstract: Imatinib mesylate (Gleevec s ), an inhibitor of the BCR-ABL tyrosine kinase, was introduced recently into the therapy of chronic myeloid leukemia (CML). Several cases of emergence of clonal chromosomal abnormalities after therapy with imatinib have been reported, but their incidence, etiology and prognosis remain to be clarified. We report here a large series of 34 CML patients treated with imatinib who developed Philadelphia (Ph)-negative clones. Among 1001 patients with Ph-positive CML treated with imatinib,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 31 publications
(23 reference statements)
10
104
2
1
Order By: Relevance
“…So far, clinical observations do not support a direct mutagenic effect of imatinib. The increase of chromosomal aberrations in Philadelphia-negative cells reported during early clinical studies of imatinib (Andersen et al, 2002;Terre et al, 2004) is not observed in patients treated upfront with imatinib. However, agents with mutagenic capacity such as cigarette smoking cause malignant disease not before decades of exposure.…”
Section: Introductionmentioning
confidence: 87%
“…So far, clinical observations do not support a direct mutagenic effect of imatinib. The increase of chromosomal aberrations in Philadelphia-negative cells reported during early clinical studies of imatinib (Andersen et al, 2002;Terre et al, 2004) is not observed in patients treated upfront with imatinib. However, agents with mutagenic capacity such as cigarette smoking cause malignant disease not before decades of exposure.…”
Section: Introductionmentioning
confidence: 87%
“…The incidence of Philadelphia independent clonal evolution during imatinib was in the range of the literature (2-17%). 1,4,5 The lower incidence of Philadelphia independent clonal evolution in patients with interferon corresponds to the small number of anecdotal reports in the literature. 1,6 Imatinib was started in 14/15 patients in chronic phase of CML.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In previous studies, the proportion of patients who had received pretreatment was higher. 1,4 The median interval from the start of therapy with imatinib or IFN to the first observation of the Ph independent clonal aberrations was 7.5 months (range 3-15 months). This corresponds to the literature, reporting median intervals from 5 to 24 months.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations